Age-Matched, Case-Controlled Comparison of Clinical Indicators for Development of Entropion and Ectropion - Kevin S. Michels; Craig N. Czyz; Kenneth V. Cahill; Jill A. Foster; John A. Burns; Kelly R. Everman (Journal of Ophthalmology)
Purpose. To analyze the clinical findings associated with involutional entropion and ectropion and compare them to each other and to age-matched controls. Methods. Prospective, age-matched cohort study involving 30 lids with involutional entropion, 30 lids with involutional ectropion, and 52 age-matched control lids. Results. The statistically significant differences associated with both the entropion and ectropion groups compared to the control group were presence of a retractor dehiscence, presence of a “white line,” occurrence of orbital fat prolapse in the cul-de-sac, decreased lower lid excursion, increased lid laxity by the snapback test, and an increased lower lid distraction. Entropion also differed from the control group with an increased lid crease height and decreased lateral canthal excursion. Statistically significant differences associated with entropion compared to ectropion were presence of a retractor dehiscence, decreased lateral canthal excursion, and less laxity in the snapback test. Conclusion. Entropic and ectropic lids demonstrate clinically and statistically significant anatomical and functional differences from normal, age-matched lids. Many clinical findings associated with entropion are also present in ectropion. Entropion is more likely to develop with a pronounced retractor deficiency. Ectropion is more likely to develop with diminished elasticity as measured by the snapback test.